Metacognitive awareness of commuter and resident students of Islamic high school in biology learning - Afifah Putri Sari; Puguh Karyanto; A. Ashadi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
There have been several studies which focus on metacognitive awareness of senior high school students done. However, the factors influence metacognitive awareness have not been widely revealed. Thus, this research aimed at distinguishing the metacognitive awareness between the commuter and resident students’ of Islamic High School in biology learning. The subject of this quantitative research was divided into two groups (commuter and resident students). The sample unit in this study consisted of three boarding schools i.e. Al-Abidin Bilingual Resident School, Al-Islam 1 Senior High School, and Majelis Taqlim Al-Quran Senior High School that were selected by purposive sampling. The participants in this study were 88 students of grade X (40 commuters and 48 residents) which were taught in the same class. The data were collected using the survey method. Metacognitive Awareness Inventory (MAI) was used to obtain the data of the students’ metacognitive awareness. The data were analyzed using independent samples t-test. The results indicated that there was a significant difference between commuter and resident students’ metacognitive awareness (p = 0.027). In addition, the commuter students performed better metacognitive awareness on biology learning than resident students.